Country-Level corporate governance and Foreign Portfolio Investments in Sub-Saharan Africa: The moderating role of institutional quality - Samuel Kwaku Agyei; Nathaniel Kwapong Obuobi; Mohammed Zangina Isshaq; Mac Junior Abeka; John Gartchie Gatsi; Ebenezer Boateng; Emmanuel Kwakye Amoah (Cogent Economics & Finance)
Given the declining volumes of Foreign Portfolio Investments (FPI) in Africa, the study sought to examine the moderating role institutional quality (INST) plays in the relationship between country-level corporate governance (CG) and FPI in Sub-Saharan Africa. This is motivated by arguments from the hierarchy of institutions hypothesis, which posits that the quality of political institutions (INST) determine the strength of economic institutions (CG) and how they affect economic activities. Data was collected on 33 SSA countries from 2009 to 2017 and analysed using the systems GMM approach. The results revealed that economies characterised by strict adherence to international auditing and reporting standards, ethically behaved firms, effective corporate boards, and well-regulated security markets tend to attract more FPI inflows, even though weak shareholder protection regimes are likely to deter FPI. We also confirmed the positive impact of robust institutions in luring FPI into SSA. Finally, we found the FPI-CG nexus to be significantly moderated by the quality of institutions prevalent in a country. This implies that the effectiveness of country-level corporate governance mechanisms can be affected by the existing institutions, thereby impacting the level of FPI an economy receives. We recommend that SSA firms take pragmatic steps to develop and practice sound CG mechanisms while the institutional setting in SSA is strengthened to harness more FPI inflows to support their economic growth agenda.